(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, middle-distance runners use different types of running equipment and natural trail running to keep their activity and fitness levels up during what we consider the annual training transition period. It is advisable to use running exercises in natural conditions before competitions and on days after high-intensity training. It was revealed that such formation of sports results of athletes depends on functional training.